Synthesis of Schiff Base having a Heterocyclic Moiety along with its Cyclized Derivatives and Study of their Antifungal Activities - Khatun, Rabeya; Islam, AS Mansarul; Hai, MA (Journal of the Bangladesh Chemical Society, 2012)
Syntheses of Schiffs base1 1-[(2, 4-difluorophenyl)-2-(1H-1, 2, 4-triazol-1-yl)] ethanone thiosemicarbazone (1A) prepared by condensation of 1-(2,4- difluorophenyl)-2-[1(H)-1,2,4-triazol-1-yl] ethanone with thiosemicarbazide, followed by cyclization2 to 2-(2,4-difluorophenyl)-2-[(1H)-1,2,4-triazol-1- ylmethyl)]-3-acetyl-5-acetylamino- thiadiazoline ( 2A), using acetic anhydride, and finally hydrolysis3 of (2A) to form 2-(2,4-difluorophenyl)-2-[(1H)-1,2,4-triazol-1- ylmethyl)]-3-acetyl-5-amino-thiadiazoline (3A), using hydrazine hydrate, all compounds having anti-fungal activities, are reported. DOI: http://dx.doi.org/10.3329/jbcs.v25i1.11765 Journal of Bangladesh Chemical Society, Vol. 25(1), 7-14, 2012